Ultrasound Guided Thoracic Paravertebral Block as an Analgesic Technique for Tracheoesophageal Fistula repair : A Case Report - Yadav, Rupesh Kumar; Malla, Sadichhya Shah; Thapa, Anupama (Birat Journal of Health Sciences, 2021)
Ultrasound has now become an eye of anaesthesiologist and has encouraged for its pervasive use. Its considerable use in the perioperative period for various invasive purposes has added an extra caution to prevent unforeseen complications over blind blocks. The ultrasound-guided thoracic paravertebral block provides excellent perioperative analgesia following thoracic surgery. It can be given as a single shot or a continuous infusion technique placing a catheter. Here the local anesthetic agent is deposited in the paravertebral space from where the spinal nerve emerges which are devoid of coverings and are sensitive to local anesthetics. Even a single-shot block provides analgesia of 4-6 dermatomal levels. The use of local anesthetics using ultrasound not only adds safety measures to minimize procedural complications but also reduces the perioperative requirement of opioids. It also helps in the reduction of postoperative pulmonary complications and early extubation following thoracic surgery. We report a case series where single-shot ultrasound-guided unilateral paravertebral blocks were used as an analgesic technique for the repair of tracheoesophageal fistula in neonates. After delivering anesthesia and confirming the correct placement of the endotracheal tube the neonate was kept on the left lateral position to undergo right thoracotomy and repair of fistula. Scanning at T4 level with a linear probe was done to identify the transverse process, pleura, costotransverse ligament, intercostal muscle, and the paravertebral space where the local anesthetic agent was deposited under aseptic precautions. Tenting of pleura was the endpoint for the completion of the block. The extensive use of various regional anesthetic technique has significantly improved the postoperative outcome of the patients along with adequate perioperative pain management.